Offshore aquaculture platform control system in intelligent fishery era - Jianbo ZHANG; Yu WANG; Xuejun NIE; Guoqing WU; Jiujun LIU; Jun YAN (物联网学报)
The control system of offshore aquaculture platform was analyzed and the collaborative control technology with edge intelligence was introduced under the open architecture of cloud computing.A distributed intelligent control mode was established.A general framework architecture of cloud-edge collaborative control system for offshore aquaculture platform and an open architecture of intelligent aquaculture cloud platform were proposed exploratively, which could be deployed flexibly with different patterns of cloud-network-edge-terminal-intelligence.A development idea of control system and an implementation scheme of could central control and edge intelligence for offshore aquaculture platform were put forward.An attempt was made to build the theoretical framework and ideology system of cloud-edge collaborative control, and it was to construct the manner with the whole process of intelligent aquaculture and land-sea linkage operation and management mode for offshore fish-farm, with a view to finally realizing the intelligent fishery industrial ecology and green sustainable development goals.